Bishops, Bourbons, and Big Mules a History of the Episcopal Church in Alabama. - Vaughn, J. Barry (Tuscaloosa : University of Alabama Press, 2013)
Bishops, Bourbons, and Big Mules tells the story of how the Episcopal Church gained influence over Alabama's cultural, political, and economic arenas despite being a denominational minority in the state. The consensus of southern historians is that, since the Second Great Awakening, evangelicalism has dominated the South. This is certainly true when one considers the extent to which southern culture is dominated by evangelical rhetoric and ideas. However, in Alabama onenon-evangelical group has played a significant role in shaping the state's history. J. Barry Vaughn.
Appendix D: Episcopal Church Membership and Population of Alabama from 1830 to 2010Appendix E: Percentage of Alabamians Twenty-Five Years Old and Older with Four or More Years of Postsecondary Education from 1950 to 2010; Abbreviations Used in Notes; Notes; Bibliography; Index.
Description based on print version record.
Keywords: Alabama -- Church history; Episcopal church -- Alabama -- History; Episcopal church -- Influence; Religion; Episcopal Church -- Alabama -- History; Episcopal Church -- Influence; Alabama -- Church history; RELIGION / Christianity / Anglican; Electronic books